Effects of Montessori Education on the Academic, Cognitive, and Social Development of Disadvantaged Preschoolers: A Randomized Controlled Study in the French Public-School System - Courtier, Philippine; Gardes, Marie-Line; Henst, Jean-Baptiste Van der; Noveck, Ira A.; Croset, Marie-Caroline; Epinat-Duclos, Justine; Léone, Jessica; Prado, Jérôme (Child Development, 2021)
Previous research on Montessori preschool education is inconsistent and prone to analytic flexibility. In this preregistered study, disadvantaged preschoolers in a French public school were randomly assigned to either conventional or Montessori classrooms, with the latter being adapted to French public education. Adaptations included fewer materials, shorter work periods, and relatively limited Montessori teacher training. Cross-sectional analyses in kindergarten (N = 176; Mage = 5–6) and longitudinal analyses over the 3 years of preschool (N = 70; Mage = 3–6) showed that the adapted Montessori curriculum was associated with outcomes comparable to the conventional curriculum on math, executive functions, and social skills. However, disadvantaged kindergarteners from Montessori classrooms outperformed their peers on reading (d = 0.68). This performance was comparable to that of advantaged children from an accredited Montessori preschool.